SP2DAS: Self-certified PKC-Based Privacy-Preserving Data Aggregation Scheme in Smart Grid. (20th January 2013) - Zhang, Jianhong; Liu, Liying; Cui, Yuanbo; Chen, Zhipeng
Abstract : Smart grid is a network of computers and power infrastructures that monitor and control energy usage by collecting data from the power grid. It can gather and distribute information about the behavior of all consumers in order to improve the efficiency, reliability, economics, safety, and sustainability of electricity services. In this paper, we propose a self-certified PKC-based privacy-preserving data aggregation scheme in smart grid to increase computation efficiency and achieve privacy protection of end users. To realize the anonymous aggregation of multidimensional data, we adopt the Chinese Remainder Theorem and homomorphic property of Paillier cryptosystem to achieve it. Comparing our scheme with Lu et al.'s scheme, the result shows that our scheme has more advantages over Lu et al.'s scheme in terms of computational costs of the user, GW, and OA. After adopting batch verification technique, the computational cost of GW is constant in our scheme, however, that of GW is linear with the number of the users in Lu et al.'s scheme. Furthermore, our scheme also supports the anonymity of the user's identity. It indicates that the local gateway GW does not know the real identity of the resident user such that the privacy of the user is better protected.